2022
DOI: 10.1371/journal.pone.0263690
|View full text |Cite
|
Sign up to set email alerts
|

Value of C-11 methionine PET/CT in patients with intracranial germinoma

Abstract: Purpose The purpose of this study was to investigate the value of C-11 methionine (MET) positron emission tomography (PET)/computed tomography (CT) in patients with intracranial germinoma (IG). Material and methods We conducted a retrospective analysis of 21 consecutive patients with pathologically confirmed IGs and eight patients with intracranial non-germinomas (INGs) located in a similar region. Clinical characteristics, imaging findings, and tumor markers such as α-fetoprotein (AFP) and β-human chorionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It may be appreciated that even with the availability of tumor tissue, the interpretation of histology may be hampered by sampling bias, tissue heterogeneity and the prominent inflammatory infiltrates frequently present in CNS GCTs. Recently, there has been increasing interest in the application of 11C-MET PET-MRI as a diagnostic tool in patients with intracranial neoplasms [40,41], including initial experience in patients with CNS GCTs [42][43][44][45][46][47]. Such a methodology offers functional data that complement the anatomical data captured by MRI alone.…”
Section: Discussionmentioning
confidence: 99%
“…It may be appreciated that even with the availability of tumor tissue, the interpretation of histology may be hampered by sampling bias, tissue heterogeneity and the prominent inflammatory infiltrates frequently present in CNS GCTs. Recently, there has been increasing interest in the application of 11C-MET PET-MRI as a diagnostic tool in patients with intracranial neoplasms [40,41], including initial experience in patients with CNS GCTs [42][43][44][45][46][47]. Such a methodology offers functional data that complement the anatomical data captured by MRI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al also described the application of 11 C-Met in intracranial germinoma, observing that 11 C-Met PET parameters had a significant association with tumor location, sex, KRAS variant, and symptoms [100]. Morales-Lozano et al also compared 11 C-Met and 18 F-FDG in multiple myeloma, and they confirmed that 11 C-Met PET/CT was more sensitive than 18 F-FDG for evaluation of myeloma tumors [101].…”
Section: Methioninementioning
confidence: 96%
“…Studies in xenograft mouse models show that treatment with recombinant methioninase, an enzyme that depletes plasma methionine levels, and/or a methionine-restricted diet can decrease tumor volume [10][11][12][13][14]. Clinically, the enhanced usage of methionine in cancer cells can be used to localize tumors with [ 11 C]-methionine positron emission tomography (MET--PET), particularly for cancers in the brain as well as organ cancers [15][16][17]. Additionally, methionine restriction has been used as a combination treatment with chemotherapy in cancer patients [9].…”
Section: Introductionmentioning
confidence: 99%